PREVALENCE FOR THE ATOPIC DERMATITIS DEVELOPMENT AT PRE-SCHOOL CHILDREN OF ALTAI KRAI - Natalja V. Shahova; Elena M. Kamaltynova; Yurij F. Lobanov; Tatiana S. Ardatova (State Scientific Center of Dermatovenereology and Cosmetology, 2018)
Aim of research: to evaluate the prevalence of atopic dermatitis at 3-6-year-old children by applying russified version of ISAAC questionnaire (International Study of Asthma and Allergies in Childhood) and to determine risk factors.Materials and Methods. Cross-section research was carried out in five places of Altai Territory (2015-2016). The prevalence of AD was determined with the help of the russified ISAAC Manual filled in by parents of the 3-5-year-old children. The ISAAC definition for current atopic dermatitis (cAD) was used in studies. Patient considered suffering from cAD if respondents' parents pointed «YES»  on three questions: «Have you ever had an itchy rash which was coming and going for at least six months?», «Have you had this itchy rash at any time in the last 12 months?», «Has this itchy rash at any time affected any of the following places: the folds of the elbows, behind the knees, under the buttocks, or around the neck, ears or eyes?».Results. The research covered 3205 children of 3-6-year-old age. The prevalence of cAD was 12.3 % (n = 393). Medically confirmed diagnosis of AD was stated only at 7.9 % (n = 254) from 393 children. It was established in logistic-regression analysis that burdened familial allergologic history increases 4,6 times the risk of the cAD development at preschool age (OR = 4.62; 95 % CI = 3.69-5.77; p < 0,01). Little duration of breastfeeding (less than six months) increases the risk of cAD development 1,6 times (OR = 1.62; 95 % CI = 1.26-2.09; p < 0.05. The prematurity, tobacco smoking at parents or the contact with pets on the first year age were not found to enhance the risk of cAD development at preschool children.Conclusion. The cAD prevalence markedly exceeds the rates of the medically confirmed diagnoses. The burdened familial history of allergic diseases and little duration of breastfeeding enhance the risk of cAD development at preschool age.